Foreign investment in real estate and housing affordability - Tajul Ariffin Masron; Abu Hassan Shaari Md Nor (Penerbit Universiti Kebangsaan Malaysia, 2016)
Foreign Investment in Real Estate (FIRE) is gradually becoming an important source of capital to many emerging markets in the world. In one hand, FIRE helps to improve the performance of real estate sector and subsequently upgrade the level of income of host countries. However, on the other hand, the inflows of FIRE may have the effect of increasing the house price. Hence, this study attempts to fill up the under-researched area of pressing issue surrounding the implications of FIRE inflows on host country’s affordability level by focusing on the experience of emerging real estate markets. The approach is specifically designed to be as informative as possible in offering the benefits and costs of luring FIRE into the host countries with respect to house affordability. Generally, this study found that FIRE is beneficial in increasing national income but might be offset by increasing house price.